СОЦІАЛЬНО-ПСИХОЛОГІЧНІ ПОКАЗНИКИ ТРИВОЖНОСТІ УЧНІВ ТА СТУДЕНТІВ СУЧАСНИХ НАВЧАЛЬНИХ ЗАКЛАДІВ РІЗНИХ ТИПІВ (World Science, 2019)
In conditions of modern daily stresses and ecologically unfavorable external factors, the level of anxiety becomes one of the leading indicators of the personality development. Anxiety predominates in the lives of modern students and very often causes a decrease in work capacity, labor productivity, communication problems and can lead to the development of various somatic diseases.At this stage, the level of anxiety becomes one of the driving factors of a number of psychological problems and is considered as an "anterior neurotic condition" and is an initial stage in behavioral disorders. Correction of anxiety and its dispel are very important in preparing students for difficult life and study situations and for learning new work. A present the number of anxious boys and girls has increased; they show signs of anxiety, uncertainty, and emotional instability. The results of recent research indicate both the increase in the number of anxious young people in comparison with the last decade, and the change in the form of anxiety, which seems to be "matured", it has become deeper and more personal.